1993
DOI: 10.1177/073168449301200508
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Proposition for a Test Method to Measure (Impact) Damage Resistance

Abstract: A preliminary proposal for a test to determine the impact damage resis tance of composite materials and their structures is offered. This test is centered on the utility of contact force as a parameter directly related to the damage that occurs during the event. This is demonstrated through work previously published as well as via new experi ments conducted on various graphite/epoxy material systems and laminates in both mono lithic laminate and sandwich configurations. Static indentation and impact tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 7 publications
0
26
2
Order By: Relevance
“…Other authors conclude that LVI and QSI are different for C/E [1,8,10,14,15,17]. Kwon and Sankar [14] and Highsmith [10] conclude that QSI leads to a larger damage zone compared to LVI, contradicting with Lagace [15] and the results of Kaczmarek [13].…”
Section: Introductioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Other authors conclude that LVI and QSI are different for C/E [1,8,10,14,15,17]. Kwon and Sankar [14] and Highsmith [10] conclude that QSI leads to a larger damage zone compared to LVI, contradicting with Lagace [15] and the results of Kaczmarek [13].…”
Section: Introductioncontrasting
confidence: 52%
“…Kwon and Sankar [14] and Highsmith [10] conclude that QSI leads to a larger damage zone compared to LVI, contradicting with Lagace [15] and the results of Kaczmarek [13]. Nettles and Hodge [17] and Breen et al [8] show results that indicate QSI leads to a more than 10 % higher load compared to LVI, the opposite is seen by Abdallah et al [1] who observe a 15 % reduction in load.…”
Section: Introductioncontrasting
confidence: 39%
See 1 more Smart Citation
“…As shown by Jackson and Poe (1993) and Lagace et al (1993), large mass impacts and static loading on monolithic laminates give virtually identical relations between damage size and peak load. Observations on the equivalence of damage resulting from static loads and quasi-static impact loads on sandwich panels have been reported by Williamson and Lagace(1993).…”
Section: Force Fmentioning
confidence: 77%
“…Several studies [5][6][7][8][9][10] show a similarity between quasi-static indentation and drop weight impact testing. While other studies [11][12][13] have shown a limit to the applicability of using quasi-static indentation to represent low velocity impact. It must be noted that there are many variables involved in these tests such as boundary conditions, specimen size, specimen thickness, stacking sequence, impactor size, impactor shape and type of fiber/resin system.…”
Section: Introductionmentioning
confidence: 99%